Feasibility Analysis of a Novel Production Method for Monolithic Integrated MEMS with Nanogaps - Hohnloser, Daniel; Schuklin, Dennis; Schmidt, Carsten; Kreitmaier, Michael; Blasini, Mario; Hagelauer, Amelie Marietta; Weigel, Robert (IEEE Sensors, 2016)
This paper analyses a novel production technique for the fabrication of microelectromechanical system (MEMS) with a gap in the scale of nanometer. The technology is based on a density-changing layer, which let a gap arise through the shrinkage of this layer. After the description of the technology, the requirements for monolithic integration and CMOS compatibility with respect to this technology are worked out. It has been discovered that there are several challenges to be overcome, especially to find a material composition which match the requirements will be important as well as to set up the process without affecting other CMOS device parameters. But if these challenges are solved the process will be suitable for various applications and enable to open up new markets.
elib2cris::1512001600,hohnloser2016
Keywords: MEMS; NEMS

Smart Sensor Framework: A Pressure Sensor for Smart Home Applications - Lieske, Tobias; Schuklin, Dennis; Hohnloser, Daniel; Reichenbach, Marc; Pfundt, Benjamin; Fey, Dietmar; Weigel, Robert (1. E|HOME-CENTER SYMPOSIUM, 2016)

Systemkonzept eines autarken und intelligenten Miniatur-Sensors für Smart Home - Schuklin, Dennis; Hohnloser, Daniel; Lieske, Tobias; Reichenbach, Marc; Bänisch, Andreas; Pfundt, Benjamin; Röber, Jürgen; Weigel, Robert; Fey, Dietmar (VDE Kongress 2016: Internet der Dinge, 2016)
Trotz der erheblichen Fortschritte im Bereich Smart Home, stellt die Installation von Hunderten von Sensoren eine der größten Herausforderungen dar. Eine mögliche Lösung für dieses Problem ist die Integration aller Komponenten innerhalb einer integrierten Schaltung. Dieser Beitrag stellt ein Konzept für ein intelligentes Sensorsystem dar, welches die wichtigsten Sensoren für das intelligente Zuhause (wie z.B. Drucksensor, Gassensor, Temperatur-, oder Lichtsensor) auf einem Chip vereint. Dadurch wird das Messen von lokalen Temperaturen, Lichtverhältnissen, Drucks und sogar Luftqualität ermöglicht. Mit diesen umfassenden Informationen können lebensunterstützende Systeme, Einbruchsdetektion, automatisierte Klimaregelung und Beleuchtungssteuerung in Räumen und vieles mehr realisiert werden. Langfristiges Ziel dieser Arbeit ist die Entwicklung eines selbst organisierenden und autonomen Netzwerks von intelligenten Sensoren im Bereich Smart Home. Mit Abmessungen von wenigen Zentimetern, kann jeder Sensor nahezu überall angebracht werden, wie zum Beispiel an einem Fenster.
elib2cris::1512001600,shuklin2016
Keywords: Smart Home; Intelligent Sensor System; MEMS Sensor; Analog to Digital Converter; Digital Processing Unit

Volumetric vertical Hall element with integrated coil - Hohnloser, Daniel; Schmidt, Carsten; Spitzlsperger, Gerhard; Weigel, Robert (Sensors and Actuators A-Physical, 2024)
Most integrated Hall elements are isolated against other parts of an integrated circuit by a pn junction. This article presents a Hall element which is entirely enclosed by a dielectric boundary and therewith electrically isolated. The used technology is a standard CMOS process which includes processing steps of the wafer backside. Experiments with the Hall element show an absolute sensitivity of 48 mV T-1. The Hall element is surrounded by an integrated coil for test capabilities without external coil. This coil has a resistance of 19 Ω and an effectiveness of 96 mT A-1.
Created from Fastlane, Scopus look-up
Keywords: Backside process; Current sensing; Hall effect; Hall element; Integrated coil